Utilization of Bittern on Green Chilli Plants Growth - Prema Kumari, P. (Asian Journal of Engineering and Applied Technology, 2018)
The growth of green chilli plants and the yield was influenced by bittern. It clearly indicated that increased in addition of bittern (lower concentration) which is enriched with secondary nutrients and micro nutrients served as a fertilizer by enhancing the fertility of the soil and inturn the yield. The plants were healthy at lower concentration. Bittern act as a promoter and induce for breaking dormancy in magnesium demanding crop such as green chilli plants.